The influence of creative thinking ability and interpersonal intelligence on students’ cooperation skills in mathematics learning - Sahara, Ani; Mahsup, Mahsup; Abdillah, Abdillah; Syaharuddin, Syaharuddin (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background:Mathematics education is crucial for developing various skills in students, including logical, analytical, systematic, interpersonal, critical, and creative thinking. These skills are essential due to the role of mathematics in science and technology, as well as its significance in achieving educational goals.Aim:The study aimed to evaluate the impact of creative thinking abilities and interpersonal intelligence on students' cooperation skills.Method:This quantitative research employed multiple linear regression analysis techniques. It involved selecting subjects, developing and validating research instruments, disseminating these instruments, and then tabulating and analyzing the data.Result:The analysis yielded the equation Y=-5.588+0.694X_1+0.366X_2, indicating a relationship between the dependent variable (Y) and the independent variables (X_1, X_2). Creative thinking ability was found to have the most significant impact on cooperation skills, contributing 69.4%. The determination value (R²) was 0.555, suggesting that 55.5% of the variance in cooperation skills could be explained by variations in creative thinking ability and interpersonal intelligence.Conclusion:The study concluded that both creative thinking ability and interpersonal intelligence significantly influence students' cooperation skills. The ANOVA test further confirmed the effect of these independent variables on the dependent variable, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁).